Photonics for the virtualization of cultural heritage - Morita, María Mercedes (2023)
This work is a brief review of the state-of-the-art of photonics applications for the virtualization of cultural heritage, focusing mainly on 3D recording and digitization techniques, virtual reality andaugmented reality. We show some LALFI-CIOp’s contributions: the improvement of the resolution andaccuracy of 3D reconstructions by using laser speckle and the combination of different imagingtechniques, such as digital photogrammetry and Reflectance Transformation imaging; thedevelopment of low-cost systems to be used by museums; and virtual and augmented realityapplications for dissemination of cultural heritage. Finally, we discuss an experience of transferring3D digitization technology to several museums and cultural heritage institutions in Argentina and wepropose an approach to extend the use of photonics in this field. Key words: photonics in cultural heritage, virtualization, 3D, photogrammetry, augmented reality.